Islamic Religious Education As Media Transformation Character - Bertha Agela; Putri Clarisa Hasibuan (Proceeding International Seminar of Islamic Studies, 2019)
This research is titled Islamic Religious Education as a media of moral change. Islamic education is UDI conscious and well-planned in preparing the students to know, who, internalize, is to import the teachings of Islam. The emerging literature is the sheer number of human beings especially learners who do not reflect Akhlaq who is both in the family, the social environment, and the school environment as taught in Islamic religious education. Whether the method or media used is not appropriate so that Akhlaq demonstrated by the learners is not in accordance with the teachings of Islamic religious education. The purpose of this research is to know the proper educational media in Islamic religious education. There are three educational media: audio, visual, and audio visual. The method used is the library of research, qualitative. It was found that educational media varies according to the students from different backgrounds.